Otimização da condutividade iônica de vitrocerâmicas condutoras por íon sódio: controle microestrutural e busca de novas composições - Muñoz, Adriana Marcela Nieto (Universidade Federal de São Carlos, 2020)
Sodium-based materials are promising candidates for manufacturing stationary storage devices such as batteries due to their low cost and the Na high redox potential. However, the corrosion, flammability, and the degradation of cell components in sodium-ion batteries caused by the high operating temperatures may be listed as disadvantages of these devices. A possible solution to these problems is to optimize the ionic conductivity of the solid electrolyte. In this work, two methods were adopted to improve the ionic conductivity of NASICON (Na-Super Ionic Conductor) solid electrolytes. The first one focused on the substitution Si4+/P5+ in the unprecedented Na1+yTi2SiyP3-yO12 (NTSP) and Na2+yAlTiSiyP3-yO12 (NATSP) series, which allows the introduction of extra Na+ ions. In the second method, Na2AlTi(PO4)3 (NATP) and Na1.8Al0.8Ge1.2(PO4)3 (NAGP) glass-ceramics with different grain sizes were obtained to establish a correlation between microstructure and ionic conductivity. For the NTSP glass-ceramics, it was observed that the inclusion of Si4+ ions in the NASICON structure promoted an increase of up to four orders of magnitude in the total conductivity. The formation of a highly conductive phase was also seen in the compositions with a high content of silicon. In the NATSP series, there was no evidence of a Si4+/ P5+ substitution since the expansion of the unit cell was not observed. This behavior was attributed to the high tendency of precursor glasses towards phase separation. Regarding the NATP and NAGP glass-ceramics, materials with average grain size from the order of nanometers to micrometers were obtained. Therefore, it was demonstrated that the glass-ceramic method is suitable to obtain materials with controlled microstructure. The microstructural variation caused an increase of up to two times in total ionic conductivity. Thus, it was concluded that aliovalent substitutions promote greater increases in ionic conductivity of NASICON materials than those obtained by changes in the grain size.
Optimización de la conductividad iónica de vitrocerámicas conductoras por ión sodio: control microestructural y búsqueda de nuevas composiciones
Optimization of ionic conductivity in Na+ conductive glass-ceramics: microstructural control and new compositions
Keywords: NASICON; Eletrólito sólido; Vitrocerâmica; Íon sódio; Solid-electrolyte; Glass-ceramic; Sodium ion; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA